FAO/IBPGR technical guidelines for the safe movement of citrus germplasm - Frison, Emile A.; Taher, M.M.; Food and Agriculture Organization of the United Nations (1991)
General recommendations are briefly outlined, followed by technical recommendations, including collecting and movement of seed, collecting and movement of budwood, therapy procedures and indexing strategy. Descriptions are given of 15 virus or virus-like diseases, 3 viroid diseases, 4 diseases caused by prokaryotic organisms and 11 other graft-transmissible diseases of unknown aetiology, including notes on causal agents, symptoms, host range, geographical distribution, transmission, therapy and indexing. (Abstract © CAB ABSTRACTS, CAB International)